A proof‐of‐concept study of an automated solution for clinical metagenomic next‐generation sequencing - Luan, Y.; Hu, H.; Liu, C.; Chen, B.; Liu, X.; Xu, Y.; Luo, X.; Chen, J.; Ye, B.; Huang, F.; Wang, J.; Duan, C. (Journal of applied microbiology, 2021)
Aims Metagenomic next‐generation sequencing (mNGS) has been utilized for diagnosing infectious diseases. It is a culture‐free and hypothesis‐free nucleic acid test for diagnosing all pathogens with known genomic sequences, including bacteria, fungi, viruses and parasites. While this technique greatly expands the clinical capacity of pathogen detection, it is a second‐line choice due to lengthy procedures and microbial contaminations introduced from wet‐lab processes. As a result, we aimed to reduce the hands‐on time and exogenous contaminations in mNGS. Methods and Results We developed a device (NGSmaster) that automates the wet‐lab workflow, including nucleic acid extraction, PCR‐free library preparation and purification. It shortens the sample‐to‐results time to 16 and 18·5 h for DNA and RNA sequencing respectively. We used it to test cultured bacteria for validation of the workflow and bioinformatic pipeline. We also compared PCR‐free with PCR‐based library prep and discovered no differences in microbial reads. Moreover we analysed results by automation and manual testing and found that automation can significantly reduce microbial contaminations. Finally, we tested artificial and clinical samples and showed mNGS results were concordant with traditional culture. Conclusion NGSmaster can fulfil the microbiological diagnostic needs in a variety of sample types. Significance and Impact of the Study This study opens up an opportunity of performing in‐house mNGS to reduce turnaround time and workload, instead of transferring potentially contagious specimen to a third‐party laboratory.